Aspekte konstruktiver Kunst : Sammlung McCrory Corporation, New York. - Rotzler, Willy (Zürich : Kunsthaus Zürich, 1977)
Agam, Yaacov ; Albers, Jozef ; Altman, Natan ; Anuszkiewicz, Richard ; Annenkow, Jurii Pawlowitsch ; Baertling, Olle ; Balla, Giacomo ; van Doesburg, theo ; Fleischmann, Adolf ; Gabo, Naum ; Gorin, Jean ; Held, Al ; Itten, Johannes ; Kelly, Ellsworth ; Kupka, Frantisek ; etc.
Aspekte konstruktiver Kunst : Sammlung McCrory Corporation, New York, Kunsthaus Zürich, 14. January bis 27. Februar 1977
Duits
kunstcatalogus